Long-term surgical outcomes of basic-type exotropia in patients with hyperopia - Hyeshin Jeon; Hee-young Choi (BMC Ophthalmology, 2023)
Abstract Background To investigate the surgical outcomes of basic-type exotropia in patients with hyperopia. Methods The medical records of patients who underwent surgery for basic-type exotropia and had been followed up for ≥ 2 years were retrospectively recruited. Patients with myopia and spherical equivalent (SE) < -1.0 diopters (D) were excluded. The patients were classified according to the SE: group H had a SE ≥  + 1.0 D, and group E had -1.0 ≤ SE <  + 1.0 D. The surgical success rate and sensory outcome were compared. Surgical success was defined as exodeviation ≤ 10 prism diopters (PD) and esodeviation ≤ 5 PD at 6 m fixation. Stereoacuity was measured using the Titmus Preschool Stereoacuity Test. Results Seventy-five patients (24 males and 51 females, mean age 5.1 ± 2.6 years, range 2.7–14.8) were included. The SE ranged from -0.9 to 4.4 and 21 patients were classified into group H and 54 into group E. The success rates were higher in group H than in group E during the entire follow-up period, but the differences were significant only at the final examination. At the final follow-up, 11 of the 21 (52.4%) patients in group H and 15 of the 54 (27.7%) in group E maintained successful alignment, whereas 10 (47.6%) and 38 (70.4%) patients exhibited recurrence. Overcorrection was exhibited in one (1.9%) patient in group E. Sensory results were comparable between the groups. The follow-up period did not differ between the two groups. The survival analysis showed no difference in the surgical results between the two groups. Conclusions Surgery for basic-type intermittent exotropia resulted in superior outcomes in patients with hyperopia compared to those with emmetropia.